Placing Time, Timing Space. Memory as Border and Line of (Hi)Stories in Richard McGuire’s Graphic Narrative Here - Balestrino, Alice (Review of International American Studies, 2018)
Alice Balestrino Sapienza University of Rome Placing Time, Timing Space. Memory as Border and Line of (Hi)Stories in Richard McGuire’s Graphic Narrative Here. This article interrogates the Cartesian understanding of time and space in narratives grounded in memorial endeavors. It focuses on the lines that define the interconnectedness between these two dimensions in relation to the introduction of the phenomenological category of memory as a third element providing a perspective on reality and blurring the borders between present and past; here and there. This composite, operative category is tested in the analysis of Richard McGuire’s graphic narrative Here (2014) that, both on the level of the format and on that of the story, outlines the porosity and the ultimate disappearance of the spatiotemporal borders by means of memories. This work conceives of a historical simultaneity that soaks a particular space in its past and of the margins of contingency that separate what pertains to History, what to individual stories and what gets forgotten instead – a representation which is studied against the background of Gilles Deleuze and Félix Guattari’s speculations on memory in A Thousand Plateaus. Keywords: Spacetime as a narrative category, Richard McGuire, Here, The American border